2018
DOI: 10.3892/ijmm.2018.3693
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interferon signaling and HCV‑RNA replication by extracellular matrix

Abstract: Although interferon (IFN)-based treatment of patients with chronic hepatitis C virus (HCV) infection is widely applied, treatment resistance is often observed in patients with advanced liver fibrosis. Given that the molecular mechanisms of IFN resistance in liver fibrosis remain elusive, the present study investigated the effects of extracellular matrix (ECM) on IFN signaling in hepatic cells. The native HuH-7 human hepatoma cell line and HuH-7 cells were stably transfected with full-length HCV-RNA fused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This pathway is involved in liver fibrosis development, which is triggered by an HCV infection through the activation of hepatic stellate cells (HSCs) [54]. The ECM is involved in the regulation of the interferon signaling pathway and HCV-RNA replication [55]. PBMCs contribute to systemic and regional inflammation and matrix remodeling in some model diseases, such as cardiac disease [56] and obesity [57].…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is involved in liver fibrosis development, which is triggered by an HCV infection through the activation of hepatic stellate cells (HSCs) [54]. The ECM is involved in the regulation of the interferon signaling pathway and HCV-RNA replication [55]. PBMCs contribute to systemic and regional inflammation and matrix remodeling in some model diseases, such as cardiac disease [56] and obesity [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that angiotensin II [ 38 ] and fibrogenic cytokines [ 39 ] contributed to the production of extracellular matrix in the liver. It was reported that excessive accumulation of extracellular matrix components, such as fibrillar type I and III collagens, fibronectin, and laminin, is a feature of liver fibrosis [ 40 , 41 ]. Another study reported that the accumulation of extracellular matrix in liver fibrosis might impair the signaling of interferon used as therapy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that excessive accumulation of extracellular matrix components, such as fibrillar type I and III collagens, fibronectin, and laminin, is a feature of liver fibrosis [ 40 , 41 ]. Another study reported that the accumulation of extracellular matrix in liver fibrosis might impair the signaling of interferon used as therapy [ 40 ]. Regarding disulfide bonds, it was reported that a disulfide bond core protein complex might constitute the nucleocapsid-like particle of HCV [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that β1-integrin-mediated signals affected the IFN signaling and promoted HCV replication. Therefore, the accumulation of extracellular matrix (ECM) in liver fibrosis may impair IFN signaling through β1integrin-mediated signaling involving ILK and FAK (38). In addition, the facilitation of HCV replication by Tax protein may partially account for more severe clinical consequences of HCV-related disease in HCV/HTLV co-infected individuals (39).…”
Section: Discussionmentioning
confidence: 99%